Communication Strategy For Handling Public Service Complaints On Instagram Account @disdukcapilkabtangerang - Sunardi, Didi; Hereyah, Yoyoh; Putra, Afdal Makkuraga (IJOSMAS, 2023)
The quality of public services is still not sufficient to achieve community satisfaction. This is indicated by the presence of public complaints about public services. The government's implementation of public services still faces ineffective and inefficient government systems, and public dissatisfaction with public services is common due to the inadequate quality of human resources. Tangerang Provincial Provincial Ordinance No. 07 of 2010 on the Implementation of Population Control stipulates that the Population and Citizenship Status Service is obliged to issue population documents within 14 working days after receiving complete and accurate required documents. says. The purpose of this study is to describe communication strategies for dealing with public service complaints on the @disdukcapilkabterang Instagram account.This research examines communication strategy, organizational communication, digital communication, new media theory, social media, social media characteristics, public characteristics (intagram followers), handling public service complaints to increase public satisfaction.This study uses a case study method with a qualitative approach, with a constructivism paradigm and data collection techniques by interviewing eight people who have an important role on social media Instagram @disdukcapilkabtangerang. With data validity techniques using data triangulation.The results showed that there was a communication strategy for handling public service complaints on Instagram @disdukcapilkabtangerang, namely the Strategy for Handling Public Service Complaints at the Tangerang Regency Population and Civil Registration Service, Interactive Communication Strategy with the Community (Follower Instagram), Strategy for Sharing Tasks for Managing Instagram @disdukcapilkabtangerang, and Implementation Strategy Complaint Handling SOP. These communication strategies have been going well since the formation of Instagram and the entry of public complaints against public services in 2019.